2003
DOI: 10.1515/mamm.2003.67.1.139
|View full text |Cite
|
Sign up to set email alerts
|

Early ontogeny of foraging behaviour in the short-nosed fruit bat Cynopterus sphinx (Megachiroptera) : preliminary results

Abstract: We used radiotelemetry to evaluate relationships between female Cynopterus sphinx and their young during the late lactation and weaning periods. Our observations suggest that young C. sphinx may be tutored by their mothers during this period. Before young are weaned, females intermittently visit their young during nightly feeding bouts. During the weaning period, mothers forage near their day roosts and are accompanied by or forage near their young. We suggest that observational learning during the late lactat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Changes in the temporal pattern of time-activity budgets are indicative of a transition stage in ontogenetic development (Lambin & Yoccoz, 2001; Gopukumar, 2003; Benton et al, 2008; Fay et al, 2016). Life-long individual monitoring that measures time-activity budgets provides a way to quantify a shift in the temporal pattern in time-activity budgets of insects.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the temporal pattern of time-activity budgets are indicative of a transition stage in ontogenetic development (Lambin & Yoccoz, 2001; Gopukumar, 2003; Benton et al, 2008; Fay et al, 2016). Life-long individual monitoring that measures time-activity budgets provides a way to quantify a shift in the temporal pattern in time-activity budgets of insects.…”
Section: Discussionmentioning
confidence: 99%
“…Mimicry of maternal behavior has been hypothesized to be an important mechanism in the development of foraging habits of young moose ( Alces alces ; Kossak 1992). Gopukumar et al (2003) suggested young short‐nosed fruit bats, Cynopterus sphinx , learn locations of profitable food patches by accompanying their mothers on foraging flights during late lactation and weaning. Observational learning of maternal foraging techniques has also been implicated in nonhuman primates (Watts 1985, van Schaik et al 2003).…”
mentioning
confidence: 99%
“…At weaning, they must replace milk from their mothers with food they obtain themselves. For many species this transition is gradual, and the young have an extended period during which to learn foraging behavior from their mothers (Carrs 1995, Horning and Trillmich 1997 a , Mann and Smuts 1999, Gopukumar et al . 2003).…”
mentioning
confidence: 99%